Toward theorizing spatial-cultural ‘othering’ in networked learning and teaching practices - Nelson, Dorothea; Parchoma, Gale (Proceedings of the International Conference on Networked Learning, 2018)
In response to networked learning community members’ calls for theorizing the underpinning causes of “othering,” this paper examines the concepts of transculturalism, boundary crossing, and third spaces to provide insights into cultural issues that can occur within networked learning environments. Suggestions are made for working from a transcultural perspective, working within and across boundaries, and teaching and learning in Third Space. We begin by examining challenges posed by increasing cultural diversities among learners in universities and then focus on how these challenges play out for both learners and tutors. In particular, we focus on issues that impact international learners who remain in their home contexts, but engage in university learning via networked learning opportunities. In the introduction, we discuss the complexities learners face when they are simultaneously “land-locked” within their own cultural and educational settings and being acculturated into new learning opportunities in a foreign university. We then draw upon transcultural scholarship to examine instances of encountering vulnerability and instability and possibilities for shifting conversations within teaching and learning contexts first to celebrating difference and then to negotiating potential academic consequences of acknowledgements of differences. We move on to discuss tensions that arise from boundary crossings that evoke discontinuities. In particular, we examine points of exclusion and inclusion where decisions are made about whose voice is heard and whose knowledge is deemed valid and relevant. Within our discussion of the complexities and tensions of boundary crossings, we draw upon the concepts of identification, coordination, reflection, and transformation. At this point, we introduce Third Space theory as a meeting point for recognizing tensions, but also problematize provision of a restrictive definition of a Third Space with a view to maintaining an open approach to theorizing spatiality that retains sufficient flexibility to propose practices that can lead to overcoming otherness. Within this context, we examine dialogical collaborative spaces where individuals share values, meanings and priorities, but also acknowledge Third Spaces as spaces as potential sites for encountering antagonism, conflict and incommensurability: tension-filled messy sites of seemingly insurmountable cultural difference and competing powers. We conclude with implications for theorizing otherness in networked learning practices.